A Literature Review of Education for Sustainable Development (ESD) in Science Learning: What, Why, and How - Vilmala, Berry Kurnia; Kaniawati, Ida; Suhandi, Andi; Permanasari, Anna; Khumalo, Minehle (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The idea of Education for Sustainable Development (ESD) is very developed lately. However, many people do not understand what, why and how ESD is. Therefore, the current article discusses obvious issue as an area for attention and related to ESD, why ESD should be, and how ESD is implemented in education, especially in science education, as well as efforts that can be made to make the implementation of ESD successful. This research is included in the parameters of the content analysis theme. This research-based paper uses literature review from various journals, articles and other text books. ESD is a new approach in the world of education. ESD consists of three dimensions, economic, social and environmental. ESD is incredibly important to apply in science learning for the success of the SDGs. There are several notable elements in the implementation of ESD in science in Indonesia, namely the government (P4TK IPA), Professional Associations such as the Indonesian Science Educators Association, Science Subject Teachers' Conferences, and Communities in the midst of society.Keywords: education for sustainable development (ESD), sustainable development goals (SDGs)